2014
DOI: 10.1016/j.chb.2013.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and predictors of alcohol reference displays on Facebook during the first year of college

Abstract: The purpose of this study was to investigate the emergence of displayed alcohol references on Facebook for first-year students from two universities. Graduated high school seniors who were planning to attend one of the two targeted study universities were recruited. Participants’ Facebook profiles were evaluated for displayed alcohol references at baseline and every four weeks throughout the first year of college. Profiles were categorized as Non-Displayers, Alcohol Displayers or Intoxication/Problem Drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 34 publications
2
38
0
2
Order By: Relevance
“…Consistent with previous research documenting college students’ frequently recording their risky drinking behaviors on SMS (Moreno et al, 2014) first-year students in this study reported observing alcohol-related content posted by peers on Facebook, Instagram, and Snapchat. Exposure to this content during the first 6 weeks of college predicted their own alcohol consumption 6 months later, even after controlling for students’ and close friends initial drinking.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous research documenting college students’ frequently recording their risky drinking behaviors on SMS (Moreno et al, 2014) first-year students in this study reported observing alcohol-related content posted by peers on Facebook, Instagram, and Snapchat. Exposure to this content during the first 6 weeks of college predicted their own alcohol consumption 6 months later, even after controlling for students’ and close friends initial drinking.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, Snapchat’s unique disappearing post feature may assure students that there will be no lasting proof of their alcohol misuse. Thus, while a number of researchers have explored the feasibility of Facebook-based alcohol interventions for college students (Ridout & Campbell, 2014; Moreno et al, 2014), data from this study suggest that college students may be better reached through Instagram and Snapchat, and if ignored, alcohol depictions on Snapchat and Instagram may even thwart Facebook-based prevention efforts.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A Facebook post is the presentation of some aspect of self on one's own virtual profile for viewing by select friends, a whole network, or even the entire web. While research has considered the content of these posts, their association with activity, and considered their possible influence (Moreno et al, 2010; Moreno, Briner, Williams, Walker, & Christakis, 2009; Moreno et al, 2014; Litt & Stock, 2011) little research has considered the predictive power of a Facebook post within a theoretical framework. It is possible, as Facebook posts may be indicative of attitude or normative expectations, that such posts operate in a similar manner as norms and attitude in predicting behavior.…”
Section: The Theory Of Reasoned Action Binge Drinking and Facebookmentioning
confidence: 99%
“…For example, some entertainment applications, or apps, accessible on smartphones seek to encourage drinking (Weaver et al 2013). Many young people's SNS profile pages are replete with alcohol and drinking-related content, both textual and visual (Brown & Gregg 2012;Egan & Moreno 2010;Griffiths & Casswell 2010;Moreno et al 2010;Moreno et al 2014). Australian university students use photos to display drinking identities, with their Facebook pages permeated with drinking-related images (Ridout, Campbell & Ellis 2011).…”
Section: New Technologies and Drinking Culturesmentioning
confidence: 98%